Progress in Soybean Genetic Transformation Over the Last Decade - Xu, Hu; Guo, Yong; Qiu, Lijuan; Ran, Yidong (Frontiers in Plant Science, 2022)
Soybean is one of the important food, feed and biofuel crops in the world. Soybean genome modification through genetic transformation has been used for trait improvement more than 4 decades. However, compared to other major crops such as rice, soybean is still recalcitrant to genetic transformation and transgenic soybean production has been hampered by limitations such as low transformation efficiency, genotype specificity, and prolonged and tedious protocols. The primary goals in soybean transformation over the last decade are to achieve high efficiency and genotype flexibility. Modifying tissue culture conditions including selection of the type of explants used, adjustment of components of culture medium, choice of selection reagents, and better understanding the transformation mechanisms of specific approaches such as Agrobacterium infection have improved soybean transformation. Transgenesis based breeding of soybean varieties with new traits is now possible through the development of improved protocols. In this review, we summarise the developments in soybean genetic transformation to date, especially focusing on the progress made using Agrobacterium-mediated methods and biolistic methods over the past decade. We also discuss current challenges and future directions.